Original sin and South-South cooperation: Insights for the Mercosur from the experience of the Asian Bond Market Initiative - Candelaria Fernández Tucci (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
The financial crises of the late 1990s in Asian and South American countries have once again highlighted the negative implications of development strategies characterized by high levels of foreign currency external indebtedness. In light of these events, South-South cooperation is conceived as an alternative to unilateral strategies to mitigate the consequences of 'original sin' and reduce macroeconomic vulnerability and financial instability. Following the financial crises of the late 1990s, member states of the Association of Southeast Asian Nations plus China, Japan and the Republic of Korea (ASEAN+3) strengthened monetary cooperation while their South American peers, under Mercosur, maintained unilateral strategies. This paper analyzes the Asian Bond Market Initiative of the ASEAN+3 countries to draw insights for monetary cooperation in the Mercosur. The results suggest that the development of a regional local currency (LCY) bond market has a significant potential to reduce countries' exposure to currency and maturity mismatch. However, the persistence of the original sin phenomenon and the emergence of other sources of instability - such as an increase in the proportion of foreign holdings of LCY bonds - impose significant challenges for policymakers. Consequently, other policy instruments, including capital controls and international reserves accumulation, should complement the development of a regional LCY bond market. Given both the recurrent beggar-thy-neighbor policies and the high levels of intra-regional exchange rate volatility in the Mercosur, this paper argues that there is no alternative to exchange rate coordination in the bloc.
Keywords: G1; G15; F3; F4; 330; Original sin; financial instability; south-south cooperation; Mercosur; Asian Bond Market Initiative; LCY bond markets